Use of Digital Tools for Horizontal Spread of Agricultural Technologies by Farmers of Kerala - Sebastian, Alan Jolly; Jeyalakshmi, G (Journal of Extension Education, 2020)
In this digital era, integration of digital tools is common in every sector and agriculture is not an exception. The present study was conducted among the farmers of Kerala who were using various digital tools, during the year 2018-2019. The sample of the study consisted of 120 farmers from three zones of Kerala. Awareness and Preference of the respondents were studied in order to find out the horizontal spread. Based on the results obtained it was found that all farmers were aware about tools like television, mobile phone and social media. Most of the farmers had selected mobile phones as the most preferred tool. Farmers were found to use mobile phones mainly for ‘crop protection’ purposes and social media for ‘marketing’ purposes.